Crustal Deformation Pattern across Yogyakarta Special Region Revealed by a Dense Geodetic Measurements - Widjajanti, Nurrohmat; Pinasti, Arinda; Pratama, Cecep; Parseno, Parseno (2019)
Special Region of Yogyakarta is one of the Indonesian regions with high seismic activity. Subduction zones and onland fault structures influence these activities. One of onland fault structures that affect this region is the Opak Fault. Therefore, deformation monitoring is required. This study used five years of geodetic data that is acquired periodically. The deformation rate of Global Navigation Satellite System (GNSS) station around the Opak fault ranging from 5.73 to 23.59 mm/yr and -30.16 to 118.61 mm/yr for horizontal and vertical components with respect to Sundaland block, respectively. Those deformation rates have been reduced by Sundaland block effect but have not deliberate error and noise from the other effects. The estimated deformation rate is used to calculate the preliminary deformation model. The strain rate analysis suggests that the western region of the fault is dominated by compression. Meanwhile, the eastern region of the fault is dominated by extension.